Environmental and economic assessment of mixed plastic waste pelletization in the Gulf Cooperation Council region - Junaid Saleem (14670322) (2024)
Pelletizing mixed plastic wastes (MPW) has gained interest as an upcycling technology and an alternative to conventional recycling. To investigate its potential, we conducted a cost analysis and life-cycle assessment (LCA) for a conceptual pelletization facility designed to produce 1 kg of pellets per batch of MPW (comprising polyethylene—PE and polypropylene—PP). This work has the following merits: (i) evaluating environmental impact (EI), cost analysis, and mechanical strength based on actual experimental data and its comparison with local and international manufacturers; (ii) enabling the evaluation of LCA impacts of MPW pellets; and (iii) emphasizing the significance of waste management in reducing EIs. The following ten EIs were assessed: climate change (CC), net energy, particulate matter formation, natural land transformation, metal depletion, marine ecotoxicity, ionising radiation, freshwater ecotoxicity, freshwater eutrophication, and terrestrial ecotoxicity. The CC of the as-synthesized pellets is 1.26 kg CO2 eq., significantly lower than the data obtained from the Gulf Petrochemicals and Chemicals Association (GPCA) and an actual plant in Gulf Cooperation Council (GCC) countries. Additionally, the net energy required for the production of 1 kg of pellets is 54.1 MJ, while the cost is around 0.55 USD. The tensile strength of MPW pellets (24.63 MPa) falls between that of PE virgin pellets (21.12 MPa) and PP virgin pellets (28.12 MPa). This suggests that the MPW pellets exhibit competitive strength characteristics, warranting its consideration for applications where moderate strength is required. Overall, the competitive cost, coupled with the reduced EIs, demonstrates the potential of pelletization as a sustainable and economically viable waste management solution. Other Information Published in: Journal of Hazardous Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jhazmat.2024.136349